A Noncovalent π‐Stacked Porous Organic Molecular Framework for Selective Separation of Aromatics and Cyclic Aliphatics. Issue 24 (12th April 2022) - Chen, Cheng; Guan, Haiyan; Li, Hengbo; Zhou, Yunzhe; Huang, Yougui; Wei, Wei; Hong, Maochun; Wu, Mingyan
Abstract: Selective separation using porous adsorbents is an energy‐efficient alternative to traditional separation techniques. Stacked porous organic molecular frameworks (POMFs) capable of noncovalent π⋅⋅⋅π interactions are emerging as a new kind of adsorbents that facilitate green separation. Here we report a robust porous molecular crystal (TAPM‐1 ), which is stabilized by multiple intermolecular π⋅⋅⋅π interactions. With its long‐range π‐stacking, TAPM‐1 has excellent hydrophobicity, thermostability, recyclability, and high selectivity for aromatics over the corresponding cyclic aliphatics. This enables TAPM‐1 to serve as the stationary phase in the high‐resolution gas chromatographic separation of benzene and cyclohexane or toluene and methylcyclohexane. Abstract : A robust π‐stacked porous organic molecular framework selectively separates aromatics over cyclic aliphatics.